Language Production in Relation to Students’ Anxiety to Speak English in Public - Rozani, Fany Amelia; Zaim, M (Universitas Negeri Padang, 2023)
This study aims to investigate and comprehend the relationships between students' anxiety levels and students’ language production. This study used descriptive quantitative approach. The participants of this study were 20 students of classes NK – 3 as first-year English department at Universitas Negeri Padang. Data was collected using the FLCAS questionnaire to measure the level of speaking anxiety and speaking performance to assess students' speaking ability. The results showed that students' speaking anxiety level was in the average mildly range. The most dominant anxiety in students is related to two main aspects, namely Communication Apprehension and Test Anxiety. Furthermore, students' speaking ability has generally reached the level of